MODEL KEPEMIMPINAN DALAM PEMBINAAN KARAKTER PESERTA DIDIK DI SMK NEGERI LABUANG KABUPATEN POLEWALI MANDAR - Djafar, Hamsiah (Idaarah: Jurnal Manajemen Pendidikan, 2017)
This study aims to describe the leadership model in the character development of learners at SMK Negeri Labuang Polewali Mandar regency, including the leadership model of school principals in shaping the character of learners, the constraints faced in the character development of learners, as well as efforts made in the character development of learners in SMK Negeri Labuang. This research uses qualitative approach with case study design. The research location is SMK Negeri Labuang Polewali Mandar Regency. Laliko Village, Campalagian District, Polewali Mandar Regency, West Sulawesi Province. The data sources of this research are principals, vice principals, teachers, and teachers BK. Data were obtained through in-depth interviews, participant observation and documentation. The data analysis technique in this research is by: 1) data reduction (data reduction) that summarizes, chooses the main things, focus on the things that are important, sought the theme and pattern and verification of data on different data sources. remove unnecessary, 2) Presentation of data {data display) after the data is reduced. 3) data verification (conclution drawing verification) that is withdrawal conclusion by using source triagulation method that is data verification method at different source. The results of the analysis can be obtained by the model of leadership in the character development of learners in SMK Negeri Labuang Polewali Mandar regency has been implemented in accordance with the education system where, his leadership as headmaster of SMK Negeri Labuang, which adheres to democratic and occasionally authoritarian leadership model has applied professionally, and coaching in the formation of the character of learners with a democratic leadership model has been applied in the activities of learners either the curricular activities of subjects as well as extracurricular activities inside or outside school